Political Public Relations: origins, challenges and applications - Gonçalves, Gisela Marques Pereira (2016)
Submitted by Gisela Gonçalves (gisela@ubi.pt) on 2016-05-04T20:41:13Z No. of bitstreams: 1 2028-7240-3-PB.pdf: 73056 bytes, checksum: 9b735bfcb85e24be898cb025a33bf35b (MD5)